Comparative study on the performance of various pretreatment and hydrolysis methods for the production of biohydrogen using Enterobacter aerogenes RM 08 from rice mill wastewater. (10th August 2015) - Ramprakash, Balasubramani; Muthukumar, Karuppan
Abstract: This study compares the performance of different pretreatment and hydrolysis methods for the efficient production of fermentable sugars from rice mill wastewater. The pretreatment and hydrolysis operating conditions were optimized. The maximum reducing sugar concentration of 16.1 g/L was obtained with combined acid and enzymatic hydrolysis. The heat, alkali, ultrasound pretreatment, acid hydrolysis and enzymatic hydrolysis showed 2.9, 2.7, 2.1, 14.2 and 15.8 g/L reducing sugar concentration, respectively. The hydrogen production was carried out using Enterobacter aerogenes RM 08 with hydrolyzate obtained from combined acid and enzymatic hydrolysis and the results showed 1.97 mol H2 /mol of sugar. The cumulative hydrogen production and the growth data of E. aerogenes RM 08 were fitted with modified Gompertz and Logistic equations. Highlights: Heat, alkali, ultrasound pretreatment, acid and enzymatic hydrolysis were studied. Combined acid and enzymatic hydrolysis gave 16.1 g/L reducing sugar. The maximum hydrogen production of 1.97 mol H2 /mol was obtained.